2015
DOI: 10.1016/j.neuropharm.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone attenuates ethanol drinking and restores extracellular glutamate concentration through normalization of GLT-1 in nucleus accumbens of male alcohol-preferring rats

Abstract: Alteration of glutamatergic-neurotransmission is a hallmark of alcohol abuse. We have previously reported that chronic ethanol-drinking downregulated glutamate transporter 1 (GLT-1) in nucleus accumbens (NAc) in male P rats in a manner that was reversed by ceftriaxone treatment. However, the effect of ceftriaxone on extracellular glutamate concentrations in NAc after chronic ethanol-drinking has not yet been studied. In the present study, male P rats were treated with ceftriaxone (100 mg/kg/day, i.p.) for five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
131
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(142 citation statements)
references
References 55 publications
9
131
2
Order By: Relevance
“…This effect was associated in part with upregulation of the two principal C-terminal splice variants of GLT-1 (GLT-1a and GLT-1b) and xCT in NAc and PFC (Alhaddad et al, 2014a; Qrunfleh et al, 2013; Rao et al, 2015b; Sari et al, 2011). Furthermore, recent study from our laboratory has confirmed the ceftriaxone-induced reduction in extracellular glutamate concentration as a consequence of increased GLT-1 expression in NAc (Das et al, 2015). Results from the present study, for the first time, demonstrated that changes in expression of GLT-1 isoforms and xCT extend beyond ceftriaxone to other cephalosporins, including cefazolin and cefoperazone.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This effect was associated in part with upregulation of the two principal C-terminal splice variants of GLT-1 (GLT-1a and GLT-1b) and xCT in NAc and PFC (Alhaddad et al, 2014a; Qrunfleh et al, 2013; Rao et al, 2015b; Sari et al, 2011). Furthermore, recent study from our laboratory has confirmed the ceftriaxone-induced reduction in extracellular glutamate concentration as a consequence of increased GLT-1 expression in NAc (Das et al, 2015). Results from the present study, for the first time, demonstrated that changes in expression of GLT-1 isoforms and xCT extend beyond ceftriaxone to other cephalosporins, including cefazolin and cefoperazone.…”
Section: Discussionmentioning
confidence: 59%
“…In conjunction with our previous findings, the present study bolsters the rationale that both cefazolin and cefoperazone treatments reduced ethanol-consumption via resumption of glutamate homeostasis in the mesocorticolimbic regions. As established in previous study from our laboratory (Das et al, 2015), we rationalize a direct translation of β-lactam-induced GLT-1 upregulation to restoration of extracellular glutamate concentration and decreased ethanol intake in P rats, and intend to establish this in our future studies. Further studies are also required to obtain a dose response effect of these drugs on ethanol dependence for their clinical effectiveness.…”
Section: Discussionmentioning
confidence: 89%
“…In cultured astrocytes, ethanol exposure alters the distribution of the glutamate transporter GLAST, shifting GLAST expression from the cytoplasm to the plasma membrane [76]. Ethanol-treated rats display lower levels of the astrocyte glutamate transporter GLT-1 [77]. Modulating glutamate transporter levels or activity alters drinking behavior.…”
Section: Cell-type Specificitymentioning
confidence: 99%
“…Treatment with the β-lactam antibiotic ceftriaxone, a potent inducer of glutamate uptake in astrocytes, increases GLT-1 expression and decreases ethanol drinking in mice, an effect dependent on AQP4 expression [79]. Ceftriaxone blocks glutamate increases in the extracellular space and increases glutamine synthetase activity in the nucleus accumbens [77]. It is effective in reducing relapse drinking in alcoholpreferring rats after long-term ethanol dependence [80] and in attenuating withdrawal [81].…”
Section: Cell-type Specificitymentioning
confidence: 99%
“…Several studies found that exposure to drugs of abuse induced a marked increase in extracellular glutamate concentration in the mesocorticolimbic regions (Smith et al, 1995, Del Arco et al, 1998, Reid et al, 2000, Williams and Steketee, 2004, Ward et al, 2009, Ding et al, 2012, Ding et al, 2013, Das et al, 2015). It has been reported that this effect can be associated with downregulation of glutamate transporters (Knackstedt et al, 2009, Changeux, 2010, Knackstedt et al, 2010, Alhaddad et al, 2014a, Alhaddad et al, 2014b).…”
Section: Role Of Glutamate Transporters In Nicotine Dependencementioning
confidence: 99%